The The influence of work environment conditions on employee performance of Cafe Sippin: English - Affandi, Irvan (Outline Publisher, 2023)
The purpose of this study was to determine the effect of working environment conditions on employee performance at Café Sippin. The research location is located on Jalan Willem Iskandar, Kenangan Baru, Kec. Percut Sei Tuan, Deli Serdang Regency. The respondents were 27 people who were employees of the café. This study used quantitative research methodology. Using questionnaire techniques conducted online through Google Form. The number of respondents in the study was 27 Café Sippin employees. This study used classical assumption tests that are associative and simple regression tests. In the results and discussion, it can be concluded that the condition of the work environment negatively affects employee performance, meaning that the deterioration in the condition of the work environment, it affects the improvement of employee performance.